2023
DOI: 10.1103/physrevb.107.085105
|View full text |Cite
|
Sign up to set email alerts
|

Pressure tuning of structure, magnetic frustration, and carrier conduction in the Kitaev spin liquid candidate Cu2IrO3

Abstract: The layered honeycomb lattice iridate Cu 2 IrO 3 is the closest realization of the Kitaev quantum spin liquid, primarily due to the enhanced interlayer separation and nearly ideal honeycomb lattice. We report pressureinduced structural evolution of Cu 2 IrO 3 by powder x-ray diffraction (PXRD) up to ∼17 GPa and Raman scattering measurements up to ∼25 GPa. A structural phase transition (monoclinic C2/c → triclinic P 1) is observed with a broad mixed phase pressure range (∼4 to 15 GPa). The triclinic phase consi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Herein, we have came up with judgment that the introduction of other magnetic ions in ilmenite-type cobaltates may bring in unexpected and complex structural variation and/or magnetic interactions, blurring the delicate balance to accomplish the sought after quantum spin liquid. In this regard, the effort to approach to the ideal Kitaev model by reducing structural distortion through application of pressure [23]in ilmenite-type compounds or exploring other systems not containing second magnetic ions [3,4], may represent an exciting future research direction, by which can afford a deeper understanding.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we have came up with judgment that the introduction of other magnetic ions in ilmenite-type cobaltates may bring in unexpected and complex structural variation and/or magnetic interactions, blurring the delicate balance to accomplish the sought after quantum spin liquid. In this regard, the effort to approach to the ideal Kitaev model by reducing structural distortion through application of pressure [23]in ilmenite-type compounds or exploring other systems not containing second magnetic ions [3,4], may represent an exciting future research direction, by which can afford a deeper understanding.…”
Section: Resultsmentioning
confidence: 99%
“…Hence the QSL materials have captured increasing attention in the field of high pressure research. [23][24][25] Among them herbertsmithite can be an ideal model system for the high pressure studies of kagome QSL materials on account of the structure-property correlation under compression. It has been observed that herbertsmithite undergoes a transition from the quantum-disordered spin liquid phase to the longrange ordered antiferromagnetic phase at 2.5 GPa and the R% 3m symmetry is preserved up to at least 5 GPa.…”
Section: Introductionmentioning
confidence: 99%